Build your nation in 5′25″: social constructions of Italy in official and user-generated videos on YouTube. Issue 2 (15th March 2017) - Buscemi, Francesco
ABSTRACT: This article focuses on the differences between the official video clip of a song dedicated to the nation and the remakes uploaded on social media by anonymous users. It argues that social media act as the semiosphere boundary, on which, for Lotman [2005. "On the Semiosphere." Sign Systems Studies 33 (1): 205–229] central dominant texts and peripheral structures meet to generate new meaning. The work draws on Lotman's semiosphere, on nation-building, and on the bottom-up construction of reality of social media. Methodologically, semiotic analysis is applied to the images of all the videos. Results show that the peripheral elements theorised by Lotman adapt to and renew the language of the centre. In fact, they adopt the same structure of the official video but expand, revitalise and deconstruct the sedimented versions of Italy that it offers. As in Lotman, the periphery challenges the dominant hierarchy. Finally, all the videos agree on relegating the woman to a secondary role.